Graphological Construction of Students' Writing as a Consideration for Differentiated Learning of Indonesian Language - Wachyudin; Hamdani; Frecelia Putri; Yusra Meldia (Studies in Learning and Teaching, 2023)
Teachers must attempt to learn about students' learning styles, psychological conditions, emotions, and personal conditions through non-cognitive diagnostic assessments. No one can learn purely visual, auditory, or kinesthetic since they are all prejudiced. Therefore, another non-cognitive approach is needed, specifically graphology. The study aims to determine changes in learning model methodology application that are appropriate to the students' conditions. The research method used by the researcher was a qualitative descriptive method. This study describes the results of analyzing students' handwriting in X-1 class of SMA Mutiara Islami Plus Bekasi. Several categories were analyzed, including the writing slant, writing line slant, writing size, word, and line spacing in writing, as well as the letter analysis (a, t, and j). The analysis results were organized in differentiated learning using a method of Inquiry Training Learning. This handwriting analysis can assist educators in discovering and determining students' interests and talents further.